Fabrication and installation of steel truss / Mohammad Firdaus Mohd Ismail - Mohd Ismail, Mohammad Firdaus (Universiti Teknologi MARA, Perak, 2018)
Roof trusses are important to bridge the space above a room and to support the roof of a building. This report was conducted for the building construction of steel truss for 2 storey link houses at Antara Gapi, Selangor. The objective of this report is to identify the method of steel truss construction. The focus was on how the steel truss were constructed and fabricated. It also determines the equipment used for installation and fabrication of steel truss on this site. The methods used to complete this report requires observation on the work carried on this site and interview sessions with related individuals. Main findings were the steel truss were easier to use and more economic also the construction procedure is easier compared to the wood truss.